ANALYSIS OF COASTAL VULNERABILITY IN AGAM REGENCY, WEST SUMATRA PROVINCE - Prayitno, Betari Erlinda; Mubarak, Mubarak; Galib, Musrifin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Natural factors such as geomorphology, waves, tides, coastal building materials, and altitude can have an impact on marine vulnerability. Coastal vulnerability is impacted by human activities such as logging of mangrove trees, tourism object activities, and manufacturing, in addition to natural influences. This study was carried out in February 2021. The goal of this study was to calculate the rate of change of the Agam Regency coastline from 2010 to 2020, as well as to map the level of vulnerability of the Agam Regency shore. According to the findings of the study. Pesisir Subdistrict, Agam Regency is classified into five levels of vulnerability, namely very not vulnerable, not vulnerable, moderate, vulnerable and very vulnerable. Very low to high levels of vulnerability can be found along the coast of Agam Regency. The annual accretion rate ranges from 0.12 to 15.98 m. The erosion rate ranges from 0.07 to 10.21 meters per year.